Elevated Omentin Serum Levels Predict Long-Term Survival in Critically Ill Patients. (27th October 2016) - Luedde, Mark; Benz, Fabian; Niedeggen, Jennifer; Vucur, Mihael; Hippe, Hans-Joerg; Spehlmann, Martina E.; Schueller, Florian; Loosen, Sven; Frey, Norbert; Trautwein, Christian; Koch, Alexander; Luedde, Tom; et al.
Abstract : Introduction. Omentin, a recently described adipokine, was shown to be involved in the pathophysiology of inflammatory and infectious diseases. However, its role in critical illness and sepsis is currently unknown. Materials and Methods. Omentin serum concentrations were measured in 117 ICU-patients (84 with septic and 33 with nonseptic disease etiology) admitted to the medical ICU. Results were compared with 50 healthy controls. Results. Omentin serum levels of critically ill patients at admission to the ICU or after 72 hours of ICU treatment were similar compared to healthy controls. Moreover, circulating omentin levels were independent of sepsis and etiology of critical illness. Notably, serum concentrations of omentin could not be linked to concentrations of inflammatory cytokines or routinely used sepsis markers. While serum levels of omentin were not predictive for short term survival during ICU treatment, low omentin concentrations were an independent predictor of patients' overall survival. Omentin levels strongly correlated with that of other adipokines (e.g., leptin receptor or adiponectin), which have also been identified as prognostic markers in critical illness. Conclusions. Although circulating omentin levels did not differ between ICU-patients and controls, elevated omentin levels were predictive for an impaired patients' long term survival.